Tomography schemes for characterizing itinerant microwave photon fields - Eichler, Christopher; Bozyigit, Deniz; Lang, Christian; Steffen, Lars; Wallraff, Andreas J; et al. (Quantum Machines: Measurement and Control of Engineered Quantum Systems: Lecture Notes of the Les Houches Summer School: Volume 96, July 2011, 2014)
This chapter illustrates the analysis of propagating microwave signals by splitters and amplifiers and shows that one can recover enough information to reconstruct the Wigner function of a microwave quantum field emitted by a qubit.<br